(untitled) (CIPEEX, 2025)
Introduction: Venous Leg Ulcer (VLU) is one of the main consequences of Chronic Venous Insufficiency (CVI) and Venous Hypertension. It develops due to retrograde blood flow and/or obstruction of vessels in the lower limbs, leading to infection or impaired wound healing. This occurs not only because of poor blood circulation, but also due to the presence of a pro-inflammatory environment, which makes the healing process difficult and prolonged¹. Consequently, the disease presents a high recurrence rate, reaching up to 70% within the first months of healing² and approximately 7% after five years or more³. Moreover, Latin America has the highest prevalence of patients with CVI who currently have or have previously had VLU, when compared to Asia, Western and Eastern Europe¹. The most affected population includes women and the elderly, as well as individuals with low income and limited education. Objective: To highlight the current knowledge regarding Venous Leg Ulcers. Methodology: This is an integrative review based on 4 scientific articles. The database used was PubMed. Inclusion criteria comprised publications no older than five years, freely accessible, and available in Portuguese or English. Articles that did not address the central research question — “What is the current understanding of venous leg ulcers?” — were excluded. Discussion: Initially, VLU manifests as microvaricosities, primarily affecting the medial region of the lower limbs. Common symptoms include pruritus with or without skin rash, acute pain, nocturnal cramps, and edema. During ulcer formation, lesions typically appear superficial, irregular, and well-defined. Compression therapy, using stockings or bandages, is recommended as the primary treatment. Additionally, topical dressings, limb elevation, mobility, hydration, and physical exercise are advised as complementary measures¹,²,³. Conclusion: VLU significantly impacts individuals’ quality of life, affecting emotional, physical, and social well-being. Physical limitations, pain, suffering, stigma, and the appearance of the lesion may lead to feelings of shame or the need to conceal the condition, resulting in social withdrawal. Consequently, many individuals refrain from seeking professional assistance and appropriate treatment²,⁴.